A novel way to deal with challenge and fear of smoke and gas evacuation during minimal invasive surgery in the current era of COVID-19 pandemic: an ingenuity with review of literature - Singh, Kaptan; Joshi, Atul S.; Khemchand, Agrawal K.; Sheoran, Hariom; Rabadiya, Priti (International Surgery Journal, 2020)
Presently COVID-19 viral transmission is a major concern among surgeons worldwide with the use of minimally invasive surgery due to creation of pneumoperitoneum. Due to this proposed concern, we sought to review the scientific data, evaluate the use of MIS and introduction of a novel concept to deal with surgical smoke and gas to prevent the risk of COVID-19 viral transmission. A review of literature of viral transmission in surgery, especially emphasizing the transmission of the COVID-19 was done. We also reviewed other surgical society guidelines and recommendations regarding surgery during this pandemic. Few studies have been performed on viral transmission during surgery, but to date there is not enough evidence to support use of MIS over open surgery or vice versa. There are societal guidelines and expert consensus on the modification of standard practices to minimize the risk of viral transmission. With every day rise in COVID-19 patients therefore consequent increase in surgeries in suspected or confirmed cases and exposure of operative staff to aerosolized particles during MIS, use of surgical smoke and gas evacuation system becomes essential. Although different available filters, insufflation systems are part of the surgical procedures but their cost and availability may concern a COVID-19 fighting or a developing nation. We introduced a novel, simple, easily available and cost effective technique to prevent and reduce the risk of viral transmission in the current era of COVID-19 pandemic.